The Concentration of Memantine in the Cerebrospinal Fluid of Alzheimer’s Disease Patients and Its Consequence to Oxidative Stress Biomarkers - Valis, Martin; Herman, David; Vanova, Nela; Masopust, Jiri; Vysata, Oldrich; Hort, Jakub; Pavelek, Zbysek; Klimova, Blanka; Kuca, Kamil; Misik, Jan; Zdarova Karasova, Jana (Frontiers in Pharmacology, 2019)
Memantine is a non-competitive N-methyl-D-aspartate (NMDA) receptor antagonist that is used as a palliative treatment for Alzheimer's disease. The clinical data are focused on the memantine pharmacokinetic profile in the periphery, and data from studies that describe the distribution in the brain and its potential pharmacodynamic effects are very rare. This is the second study examining the memantine concentrations in cerebrospinal fluid. The previously published study enrolled only six patients, and only three of them were theoretically in a steady state. In our study, we recruited 22 patients who regularly used a standard therapeutic dose of memantine (20 mg per day, oral administration) prior to the sample collection. Patients were divided into four groups, depending on the time of plasma and cerebrospinal fluid sampling: 6, 12, 18 and 24 hours after memantine administration. The cerebrospinal fluid samples were also assessed for selected oxidative stress parameters (malondialdehyde, 3-nitrotyrosine, glutathione, non-protein thiols and non-protein disulfides). The plasma/CSF ratio for all time intervals were within the range of 45.89 % (6 hours) – 55.60 % (18 hours), which corresponds with previously published findings in most patients. The other aim of our study was to deduce whether the achieved “real” memantine concentration in the central compartment was sufficient to block NMDA receptors. The IC50 value of memantine as an NMDA antagonist is in micromolar range; the lowest limit is 112 ng/mL (GluN2C), and this value was achieved only in three cases. The memantine cerebrospinal fluid concentration did not reach ¼ of the IC50 value in 5 cases (one patient was excluded for noncompliance); therefore, the potency of memantine as a therapeutic effect in patients may be questionable. However, it appears that memantine therapy positively affected the levels of some oxidative stress parameters, especially non-protein thiols and 3-nitrotyrosine.